2010
DOI: 10.1098/rspb.2009.2055
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural consequences of sensory plasticity in guppies

Abstract: Sensory plasticity, whereby individuals compensate for sensory deprivation in one sense by an improvement in the performance of an alternative sense, is a well-documented phenomenon in nature. Despite this, the behavioural and ecological consequences of sensory plasticity have not been addressed. Here we show experimentally that some components (vision and chemoreception) of the sensory system of guppies are developmentally plastic, and that this plasticity has important consequences for foraging behaviour. Gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 41 publications
1
42
0
Order By: Relevance
“…That is, fish behavior in turbid versus clear water depended on whether they were reared in turbid versus clear water. This result underscores the general importance of considering developmental rearing conditions in determining behavioral responses to changing environments (Chapman et al 2010). It is notable that fish decreased baseline activity in whichever environment was novel with respect to their developmental treatment condition.…”
Section: Behavior In Turbid Watermentioning
confidence: 59%
“…That is, fish behavior in turbid versus clear water depended on whether they were reared in turbid versus clear water. This result underscores the general importance of considering developmental rearing conditions in determining behavioral responses to changing environments (Chapman et al 2010). It is notable that fish decreased baseline activity in whichever environment was novel with respect to their developmental treatment condition.…”
Section: Behavior In Turbid Watermentioning
confidence: 59%
“…Many fish species rely on vision as their main source of Communicated by J. Lindström information, for example, with respect to foraging and antipredator behaviour (Guthrie and Muntz 1993). Therefore, changes in the natural environment that modify the optical properties of water or the visibility per se may have important consequences for the biology of fishes (Endler 1992;Utne-Palm 2002;Chapman et al 2009Chapman et al , 2010Sluijs et al 2010).…”
Section: Introductionmentioning
confidence: 96%
“…The ability to compensate for a restricted use of one sense, for example triggered by a limited visual environment, by the enhanced acuity in another sense (''compensatory plasticity hypothesis'': Rauschecker and Kniepert 1994), is known as ''sensory plasticity''. A study by Chapman et al (2010) on guppies, for example, showed a sensory switch from vision to chemoreception (smell/taste) as response to limited availability of light during rearing.…”
Section: Introductionmentioning
confidence: 98%